2019
DOI: 10.4236/jgis.2019.116039
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Location-Allocation and Accessibility Models in GIS to Improve Urban Planning for Health Services in Al-Madinah Al-Munawwarah, Saudi Arabia

Abstract: In this study, accessibility and location-allocation models have been integrated into GIS to improve spatial planning and environmental sustainability of health services in Al-Madinah Al-Munawwarah. This integration provides a planning framework in order to check the efficiency of the spatial allocation of health services and to generate alternatives either by proposing an active service or to improve an existing one. To achieve these objectives, the accessibility to the service area was analyzed within the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
0
12
0
2
Order By: Relevance
“…It seems logical that government institutions or even the private sector focus on allocating healthcare services in densely populated areas in order to provide access to the majority of the population. For instance, it was found that the population of the central districts in Al-Madinah, Saudi Arabia can easily access health services with the least distance and fastest time because of the high spatial concentration of these services at the level of central districts [69]. Moreover, according to Luo et al [18], the central urban areas of Wuhan have a higher or the highest level of medical accessibility that is attributed to the spatial concentration for most population and medical services in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…It seems logical that government institutions or even the private sector focus on allocating healthcare services in densely populated areas in order to provide access to the majority of the population. For instance, it was found that the population of the central districts in Al-Madinah, Saudi Arabia can easily access health services with the least distance and fastest time because of the high spatial concentration of these services at the level of central districts [69]. Moreover, according to Luo et al [18], the central urban areas of Wuhan have a higher or the highest level of medical accessibility that is attributed to the spatial concentration for most population and medical services in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…The results of application of location/allocation models, presented in Table 3 and Figures The same approach has been used to improve access to healthcare in Saudi Arabia (Abdelkarim, 2019;El Karim and Awawdeh, 2020). In general, location/allocation problems (p-median, maximum covering location problem), E2SFCA A i variance reduction, and their combination can be used to achieve spatial optimization towards a balance of efficiency and equality (Wang, 2020).…”
Section: Articlementioning
confidence: 99%
“…The relationships between health, place and space including analyses of geographical patterns of healthcare access, monitoring, and intervention planning is well understood (Foley, Charlton, & Fotheringham, 2009;Shen & Tao, 2022). A framework for examining the use of health services and producing alternatives, either to suggest an efficient service or to improve health services, is provided by the integration of location-allocation and accessibility models (Abdelkarim, 2019). The goal of facility location decisions, also known as location-allocation problems, was to optimize the location of facilities to reduce cost and distance from demand and supply regions (Cooper, 1963).…”
Section: Literature Review 21 Location-allocation Model In Public Hea...mentioning
confidence: 99%